A Trusted and Energy Efficient Approach for Cluster-Based Wireless Sensor Networks. (10th April 2016) - Wang, Tianshu; Zhang, Gongxuan; Yang, Xichen; Vajdi, Ahmadreza
How to improve both security and energy efficiency is one of the most prominent issues in wireless sensor networks (WSNs). In this paper, we present a trusted and energy efficient approach for cluster-based WSNs. The approach offers (i) trusted hardware module design; (ii) energy-efficient clustering algorithm; and (iii) network operation. In the cluster-based WSNs, every cluster head is equipped with a designed trusted hardware module (TM) to improve security. Then, for improving the energy efficiency of the network, a trusted hardware based energy efficient clustering (TEEC) algorithm is proposed to select appropriate cluster heads. In the network operation, we use TEEC algorithm to perform clustering and apply TMs to achieve security functions. The analysis shows that our approach does well in resisting the attacks such as data confidentiality attack, data integrity attack, and compromise node attack. In addition, experimental results show that the TEEC algorithm makes more balanced clusters with the variance value of loads around 50% and prolongs the life cycle of the network at least 10% compared to traditional methods.